2022
DOI: 10.48550/arxiv.2205.02824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Locomotion via Reinforcement Learning

Abstract: Agile maneuvers such as sprinting and high-speed turning in the wild are challenging for legged robots. We present an end-to-end learned controller that achieves record agility for the MIT Mini Cheetah, sustaining speeds up to 3.9 m/s. This system runs and turns fast on natural terrains like grass, ice, and gravel and responds robustly to disturbances. Our controller is a neural network trained in simulation via reinforcement learning and transferred to the real world. The two key components are (i) an adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Training on hardware can lead to better performance, but the range of behaviors that can be learned has so far been limited because of safety and data efficiency concerns. Similar to our work, prior work has shown that learned gaits can achieve higher velocities compared with scripted gaits (49)(50)(51). However, the gaits have been specifically trained to attain high speeds instead of emerging as a result of optimizing for a higher level goal.…”
Section: Discussionmentioning
confidence: 77%
“…Training on hardware can lead to better performance, but the range of behaviors that can be learned has so far been limited because of safety and data efficiency concerns. Similar to our work, prior work has shown that learned gaits can achieve higher velocities compared with scripted gaits (49)(50)(51). However, the gaits have been specifically trained to attain high speeds instead of emerging as a result of optimizing for a higher level goal.…”
Section: Discussionmentioning
confidence: 77%
“…Another approach to generating running and jumping controllers is through deep reinforcement learning. For example, fast trot-running [16], [17] and bounding [18] have autonomously emerged end-to-end through learning frameworks. Advanced skills can also be learned by incorporating terrain-awareness for tasks such as climbing and jumping gaps [19], or rough terrain locomotion in the wild [20].…”
Section: Recent Work Extends Such Single Jumps With Model Predictivementioning
confidence: 99%
“…It can also build large-scale realistic complex scenes, and its underlying PhysX engine can accurately and realistically model and simulate the motion of objects. Therefore, more researchers have begun to use Isaac Gym as the implementation and verification platform of DRL algorithm [35][36][37][38] .…”
Section: Simulatormentioning
confidence: 99%